Dollhouse And Mrs. Potato Head : Figurative Language Used In Melanie Martinez Selected Songs - Khilda Umi Rahmah; Wiutami Danesha Afrianto; Aidil Syah Putra (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
This study explores the use of figurative language in Melanie Martinez's songs "Dollhouse" and "Mrs. Potato Head," highlighting how these linguistic elements contribute to the thematic and emotional depth of the lyrics. Through a detailed analysis, the research identifies and interprets various figures of speech, including metaphors, similes, and personifications, which Martinez employs to address complex themes such as family dynamics, societal pressures, and self-image. The findings reveal that figurative language in "Dollhouse" vividly portrays the façade of a seemingly perfect family life, while "Mrs. Potato Head" uses similar techniques to critique beauty standards and the pursuit of physical perfection. By examining the intricate use of figurative language in these songs, the study underscores Martinez's ability to convey powerful messages and evoke emotional responses, enhancing listeners' engagement and understanding of the underlying issues. This analysis not only contributes to the appreciation of Martinez's lyrical artistry but also provides insights into the broader implications of figurative language in contemporary music.